Cascading of the as-built microstructure through heat treatment and its role on the tensile properties of laser powder bed fused Inconel 718 - Radhakrishnan, R. Jayaraj (2022)
The microstructures and mechanical properties of the Ni based superalloy, Inconel 718 (IN718), which was additively manufactured using the laser beam powder bed fusion (LB-PBF) technique in the as-built (AB) and heat treated (HT) conditions were investigated, with emphasis on the microstructural evolution from the AB to HT conditions and, in turn, on the tensile properties. Optimized LB-PBF parameters in two different processing instruments led to distinct textures in the AB alloys, which, in turn, impart diverging combinations of strength-ductility properties. These variations are rationalized by recourse to an analysis of the effective mean free path for dislocations within the solidification cell structures. Amongst the five different heat treatment schedules examined, one set led to the retention of as-built grain morphology and texture with the formation of the δ phase that is oriented at either ±45° to build direction in the alloy with 〈100〉 texture or at 0/ ± 90 ° in the alloy with 〈110〉 texture. The second set of heat treatments led to complete recrystallization, and hence loss of as-built microstructural signatures, with no δ phase. The critical role of δ phase in determining the grain growth kinetics and subsequently the anisotropy in mechanical properties of heat treated IN718 was elucidated. The absence of δ phase was found to enhance both strength and ductility, while its occurrence in the alloy with 〈110〉 texture along the build direction reduces ductility markedly. Implications of these results in terms of developing and designing the processing strategies of LB-PBF Inconel 718 with tailored microstructures and good mechanical properties are discussed.